2015
DOI: 10.1002/eet.1690
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Governance, Decentralization and Environmental Prioritization: How is it working in rural development policy in Scotland?

Abstract: Adopting a 'multilevel' governance system and environmental prioritization for the Rural Development Policy (RDP) in Europe are key actions recommended by the European Commission. Member States can decide how and to what extent these actions are incorporated into their RDP design. Through 61 semi-structured in-depth interviews with institutional stakeholders, this study assesses the application of these recommendations in RDP in Scotland. The findings indicate that many barriers to effective implementation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In this context, the (Yang et al, 2015) study showed that there was a significant impact on the decentralization of economic growth. However, this study did not elaborate on the role of other factors that may have an impact as different application environments on the one hand and dimensions of decentralization on the other side.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, the (Yang et al, 2015) study showed that there was a significant impact on the decentralization of economic growth. However, this study did not elaborate on the role of other factors that may have an impact as different application environments on the one hand and dimensions of decentralization on the other side.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In MLG, a key challenge is integrating supranational policy into national and local government policy. As a result, MLG-ESC policies must allow local governments to craft and apply ESC policies in ways that reflect the local, situational context, an argument consistent with SCP theory (Yang, Rounsevell, and Haggett 2015).…”
Section: Multilevel Governance and The Environmentmentioning
confidence: 99%
“…There are numerous examples of MLG-ESC policy that address cooperative supranational climate change policy (Betsill and Bulkeley 2006), forestation/deforestation policies (Bottazzi and Dao 2013), decentralization of energy infrastructures (Goldthau 2014), water recycling (Hughes 2013), governance of marine ecosystems (Gruby and Basurto 2013), and forest management practices (Bixler 2014), among others. These policies vary significantly due to the MLG argument that local governance must be allowed to adapt supranational policy to local contexts to improve their efficiency (Yang, Rounsevell, and Haggett 2015). This approach is employed because local or community-level governments are closest to the manifestation of the problem being addressed and, thus, better able to recognize how that problem plays out within the context of their community; and it supports the SCP suggestion that a “one-size-fits-all” ESC policy may not be the most effective response to environmental harms.…”
Section: Multilevel Governance and The Environmentmentioning
confidence: 99%
“…Forestry decentralization, for example, should allow local governments to take on greater decision-making roles with the intention of providing more targeted and informed decisions (Larson and Petkova 2011). Yet decentralization efforts are often limited by ongoing centralized controls, followed by heavy bureaucratic burdens (Larson et al 2007;Yang et al 2015a). The expectation from more centralized systems is that policies will be rolled out and implemented more uniformly.…”
Section: Introductionmentioning
confidence: 99%